Stereotactic Body Radiation Therapy (SBRT) Combined With Chemotherapy for Unresected Pancreatic Adenocarcinoma - Gurka, Marie K. (Am J Clin Oncol, 2017)
OBJECTIVES: The role of radiation therapy in the management of unresectable pancreatic cancer is controversial. One concern about concurrent chemoradiation relates to the timing of chemotherapy. In contrast to conventional radiation therapy, stereotactic body radiation therapy (SBRT) delivers high doses in a shorter duration resulting in minimal disruption in chemotherapy. Here, we report our results of patients treated with SBRT and chemotherapy for inoperable pancreatic cancer. MATERIALS AND METHODS: Thirty-eight patients treated with SBRT and chemotherapy for locally advanced, borderline resectable, and medically inoperable pancreatic cancer at our institution from January 2008 to December 2012 were included in this retrospective analysis. Treatment was delivered in 5 fractions of 5 or 6 Gy per fraction over 5 days. Toxicities were scored using the Common Terminology Criteria for Adverse Events version 3. Survival was calculated using the Kaplan-Meier method. RESULTS: The median age was 70 years (range, 45 to 90 y). Eastern Cooperative Oncology Group performance status ranged from 0 to 3. Thirty-four patients received concurrent chemotherapy. Four patients received sequential chemotherapy. Median overall survival was 14.3 months and median progression-free survival was 9.2 months from diagnosis. From radiation, overall survival and progression-free survival were 12.3 and 6.8 months, respectively. The overall local control rate was 79%. Acute toxicity was minimal. Severe late SBRT-related toxicities included 1 grade 3 gastric outlet obstruction, 1 grade 4 biliary stricture, and 1 grade 5 gastric hemorrhage. CONCLUSIONS: SBRT combined with chemotherapy for unresectable pancreatic cancer is convenient, feasible, and generally well tolerated. Outcomes of SBRT combined with chemotherapy compare favorably to results obtained with chemotherapy and conventional radiation therapy.